Camera traps reveal extensive anthropogenic impacts inside protected areas in Bangladesh - Raf Ana Rabbi Shawon; Md. Matiur Rahman; Md Mehedi Iqbal; Junji Moribe (PLoS ONE, 2026)
Camera traps serve as an essential tool for monitoring the wildlife habitat while simultaneously detecting and assessing various anthropogenic intrusions within protected areas (PAs). This study aims to monitor anthropogenic intrusions within the PAs of Satchari National Park (SNP) of Sylhet in Bangladesh. The study was conducted from May 2024 to April 2025 using camera traps that were systematically installed in 19 different stations inside the SNP. The study detected a total of 8,042 counts of videos that provided a large number of various anthropogenic intrusions inside SNP. Importantly, the study significantly revealed several anthropogenic intrusions including hunting, poaching, wood collection, tourism, and livestock grazing inside SNP. Notably, our results demonstrated that hunters and poachers in SNP carried firearms and traditional tools, including bows and arrows, confirming active hunting practices and diverse hunting methods. Moreover, the temporal co-efficient analysis indicated that anthropogenic activities were associated with shifts in wildlife activity patterns and temporal dynamics. The current study indicates that such disturbances could potentially impact and disrupt the ecological balance and pose a threat to the long-term persistence of wildlife within PAs of SNP. The present study also suggests the importance of maintaining anthropogenic intrusions at minimal levels in SNP and strengthening eco-tourism management to reduce conflicts between wildlife conservation and human recreation. To the best of our knowledge, this is the first camera trap monitoring to comprehensively evaluate anthropogenic activities in SNP of Bangladesh.